Immune responses to cholera in children. Issue 4 (2012) - Leung, Daniel T; Chowdhury, Fahima; Calderwood, Stephen B; Qadri, Firdausi; Ryan, Edward T
Cholera is a severe acute dehydrating diarrheal disease caused by Vibrio cholerae O1 or O139 infection, and is associated with significant mortality and morbidity globally. Although young children bear a high burden of the disease, currently available oral vaccines give a lower efficacy and shorter duration of protection in this group than in adults. According to the studies of natural infection, young children achieve comparable systemic anti- V. cholerae antigen-specific antibody, gut-homing antibody-secreting cell and memory B-cell responses as adults. Studies on innate and cell-mediated immune responses are lacking in children, and may offer important insights into differences in vaccine efficacy. The impact of host factors such as malnutrition, genetics and coinfection with other pathogens also remains to be fully defined.